2000
DOI: 10.1006/gyno.2000.5837
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Conservation in Primary and Metastatic Epithelial Ovarian Cancer

Abstract: Purpose. The aim of this study was to compare the overexpression of specific biomarkers in primary advanced and recurrent epithelial ovarian cancers.Methods. Biomarker expression by epithelial ovarian cancer specimens from primary and metastatic sites was examined by immunohistochemistry and flow cytometry. Biomarker expression by subpopulations of tissues consisting of matched pairs of synchronous and metachronous lesions was also studied.Results. A total of 3173 epithelial ovarian cancer specimens were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
4
21
1
Order By: Relevance
“…This data study suggest that aneuploidy if ever demonstrated in histologically confirmed borderline tumors should prompt more sampling of the tumor and a close follow up. Similar results have been seen in by other studies [53][54][55][56] . Lai et al [55] found that reproducible DNA aneuploidy of high DI may be predicting a poor outcome in 50 borderline ovarian cases.…”
Section: Discussionsupporting
confidence: 93%
“…This data study suggest that aneuploidy if ever demonstrated in histologically confirmed borderline tumors should prompt more sampling of the tumor and a close follow up. Similar results have been seen in by other studies [53][54][55][56] . Lai et al [55] found that reproducible DNA aneuploidy of high DI may be predicting a poor outcome in 50 borderline ovarian cases.…”
Section: Discussionsupporting
confidence: 93%
“…All metastases were either homogeneously positive or negative. Tewari et al (32) found that H ER -2 was expressed in 11% of metastases from epithelial ovarian cancer (n ¾ 1444) and in 12% of primary tumours (n ¾ 730). H ER -2 expression did not signi cantly differ in primary and metastatic sites from the same patient (n ¾ 38).…”
Section: Discussionmentioning
confidence: 99%
“…19,20,[23][24][25]28,29,39,42,46,[49][50][51]53,58,[61][62][63][64]66,[71][72][73][74][76][77][78][79]82,83,85,87,90,95,97,99,103,104,106,109,110,114 Overall, p53 was detected in 39% of the Stage I/II tumors and 55% of the Stage III/IV tumors ( Again, although antibody specific estimates by tumor grade varied considerably (data not shown), a consistent pattern emerged. Overall, the proportion of tumors positive for p53 was lowest among the Grade 1 tumors and highest among the Grade 3 tumors (Fig.…”
Section: Carcinomamentioning
confidence: 99%